History review of nuclear reactor safety. (October 2018) - Gu, Zhixing
Highlights: The history of the birth for atomic energy is reviewed. The history of the birth for nuclear reactor safety is reviewed. The history of the development for nuclear reactor safety is reviewed. The history of the dilemma for nuclear reactor safety is reviewed. The history of the rebirth for nuclear reactor safety is reviewed. Abstract: With the occurrence of the three major nuclear accidents, nuclear safety issues have become the lifeblood for nuclear power development in the world. Understanding the history of nuclear reactor safety is of great significance to improve the safety of the future nuclear power. In this article, the histories of nuclear reactor safety development are reviewed in terms of the "birth of atomic energy", "birth of nuclear reactor safety", "development of nuclear reactor safety", "dilemma of nuclear reactor safety", "rebirth of nuclear reactor safety".